The Total Performance Scorecard: Case at UIN Syarif Hidayatullah Jakarta - Suhendra Suhendra (ETIKONOMI, 2016)
This study aims to identify and analyse Total Human Resources Champions Management in relation to the Total Performance Scorecard. This study uses primary data by distributing questionnaires to the respondents, the 30 heads of department, 60 lecturers, 30 administrative staffs and 60 students of UIN Syarif Hidayatullah Jakarta. Partial Least Square (PLS) had been used. Results from this study showed that all dimensions of Total Human Resources Champions Management (Human Resources Strategic Management, Infrastructure Management Firm, Management Employee Contribution, Management of Transformation and Changes, Spiritual and Campaign Management, Talent Management) affected on Total Human Resources Champions Management, furthermore, Total Human Resources Champions Management has a significant positive effect on the Total Performance Scorecard course at UIN Syarif Hidayatullah Jakarta.DOI: 10.15408/etk.v15i2.3864